Value of Flexibility in Gas Pipeline Investments - Katerina Shaton (Innovations and Strategies for Logistics and Supply Chains: Technologies, Business Models and Risk Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 20, 2015)
Investments in upstream gas transport pipelines are characterized by significant economy of scale: there is a low additional cost to establish capacity in excess of the committed volumes. The excess capacity provides flexibility for cost-efficient expansions of the transportation system if there are new discoveries in the future. Therefore, investments in excess pipeline capacity may have a significant value for the gas sector in general, which is disregarded by the private decision-makers. The flexibility to expand the transportation network can be regarded as an option, which can be exercised if there are new discoveries and market conditions are favorable. The objective of this paper is to consider how Real Options thinking can be applied to estimate the monetary value of the flexibility provided by excess capacity in gas transport pipeline investments. The proposed method is based on the binomial lattices and allows including both market and project-specific risks. An example demonstrates how this value can be used by a public decision-maker in the evaluation of infrastructure projects in the Norwegian gas transport sector.
10419/209189; https://econpapers.repec.org/RePEc:zbw:hiclpr:20
Keywords: 650; Gas pipeline Investments; Excess Capacity; Value of Flexibility; Real Options